2019
DOI: 10.1111/tbed.13397
|View full text |Cite
|
Sign up to set email alerts
|

Estimating foot‐and‐mouth disease (FMD) prevalence in central Myanmar: Comparison of village headman and farmer disease reports with serological findings

Abstract: The impacts of foot‐and‐mouth disease (FMD) on food security in developing countries are difficult to quantify due to the scarcity of accurate data on the prevalence and incidence of affected villages. This is partly due to resource constraints as well as the logistical challenges of conducting regular diagnostic testing in remote locations. In this study, we used descriptive analysis and latent class analysis (LCA) models to analyse data collected during a field survey of 160 villages in central Myanmar in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…The results were similar for both Laos and Myanmar, suggesting this might be a pattern which is common throughout the region. This is supported by data from Myanmar showing that clinical FMD occurred less frequently than exposure and seroconversion (5). The FMDV 3D RT-qPCR has a diagnostic specificity of close to 100% (31) and a diagnostic sensitivity (DSe) of 97.7% (32), therefore low rates of false positivity may occur.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The results were similar for both Laos and Myanmar, suggesting this might be a pattern which is common throughout the region. This is supported by data from Myanmar showing that clinical FMD occurred less frequently than exposure and seroconversion (5). The FMDV 3D RT-qPCR has a diagnostic specificity of close to 100% (31) and a diagnostic sensitivity (DSe) of 97.7% (32), therefore low rates of false positivity may occur.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies undertaken in these countries as part of the PCP-FMD demonstrated widespread exposure of cattle, with up to 56% of villages in central Myanmar demonstrating serological evidence of FMDV exposure (5), 51% of large ruminants at a Laos slaughterhouse testing positive on serology (20) and the circulation of multiple strains of FMDV (types O, A, and Asia 1) (23,24). Seropositivity is greater than predicted by either formal outbreak reporting (25) or village headman observations (5). This suggests that research is needed to better define the role played by subclinical animals in FMDV transmission in Myanmar and other FMDV-endemic countries with similar husbandry and ecological conditions.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Even though the vaccine with high efficacy is available, the different types of strains (i.e. serotype Asia 1, O/ME-SA/Ind-2001d, and O/SEA/Mya-98) could be challenging for disease control and which may further need for vaccine matching with local strain [ 17 – 19 , 22 , 23 ]. The most prevalent FMDV strains are serotype O and A whereas serotype Asia 1 was newly detected in Myanmar in 2005 which could not be clearly explained by the source of origin; and since the dynamic of disease transmission is so complicated, vaccine matching is another challenging for disease control by vaccination for low-income country with limited resource like Myanmar [ 16 , 22 , 24 – 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…serotype Asia 1, O/ME-SA/Ind-2001d, and O/SEA/Mya-98) could be challenging for disease control and which may further need for vaccine matching with local strain [ 17 – 19 , 22 , 23 ]. The most prevalent FMDV strains are serotype O and A whereas serotype Asia 1 was newly detected in Myanmar in 2005 which could not be clearly explained by the source of origin; and since the dynamic of disease transmission is so complicated, vaccine matching is another challenging for disease control by vaccination for low-income country with limited resource like Myanmar [ 16 , 22 , 24 – 27 ]. Due to the awareness, limited resources and vaccination practice especially in rural areas where the majority of traditional backyard farming is implemented, FMD has been still threatening the livestock production especially in developing countries [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%